Development of a 2-inch GaN wafer by using the oxide vapor phase epitaxy method. (22nd May 2019) - Takino, Junichi; Sumi, Tomoaki; Okayama, Yoshio; Nobuoka, Masaki; Kitamoto, Akira; Imanishi, Msayuki; Yoshimura, Masashi; Mori, Yusuke
Abstract: From the previous studies, one of the challenges in the oxide vapor phase epitaxy (OVPE) method was suppressing poly-crystal generation for thick GaN growth. In this study, thick GaN growth was realized by controlling the supersaturation ratio using thermodynamic analysis, and an OVPE-GaN wafer of 300 μ m-thick was obtained. As a result of evaluating the quality of the OVPE-GaN wafer, it was confirmed that both the high oxygen concentration and the high crystallinity were achieved. The resistivity was 7.75 × 10 −4 Ω cm and the threading dislocation density (TDD) was 8.8 × 10 4 cm −2 . It was newly found that the OVPE method can reduce TDD from the order of 10 6 cm −2 to the order of 10 4 cm −2 with a grown thickness of less than 500 μ m. From these results, it was proved that the OVPE method has a great potential of manufacturing low resistivity and low TDD GaN wafers.